Preventing Compulsory Admission to Psychiatric Inpatient Care: Perceived Coercion, Empowerment, and Self-Reported Mental Health Functioning after 12 Months of Preventive Monitoring - Lay, Barbara; Drack, Thekla; Bleiker, Marco; Lengler, Silke; Blank, Christina; Rössler, Wulf (Frontiers in Psychiatry, 2015)
Objective: To evaluate effects of a preventive monitoring program targeted to reduce compulsory re-hospitalization and perceived coercion in patients with severe mental disorder. We analyze patient outcomes in terms of perceived coercion, empowerment and self-reported mental health functioning at 12 months. Methods: The program consists of individualized psycho-education, crisis cards and, after discharge from the psychiatric hospital, a 24-month preventive monitoring. In total, 238 psychiatric inpatients who had had compulsory admission(s) during the past 24 months were included in the trial. T1-assessment 12 months after baseline was achieved for 182 patients. Results: Study participants reported lower levels of perceived coercion, negative pressures and process exclusion, a higher level of optimism, and a lesser degree of distress due to symptoms, interpersonal relations and social role functioning (significant time effects). However, improvements were not confined to the intervention group, but seen also in the TAU group (no significant group or interaction effects). Altered perceptions were linked to older age, shorter illness duration, female sex, non-psychotic disorder, and compulsory hospitalization not due to risk of harm to others. Conclusion: Our findings suggest that changes in the subjective perspective were fuelled primarily by participation in this study, rather than by having received the specific intervention. The study contributes to a better understanding of the interaction between 'objective' measures (compulsory readmissions) and patients’ perceptions and highlights the need for treatment approaches promoting empowerment in individuals with a history of involuntary psychiatric hospitalizations.